1989
DOI: 10.1161/01.hyp.13.6.630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium carbonate on blood pressure in normotensive and hypertensive people.

Abstract: Forty-seven patients with mild hypertension and 48 normotensive patients entered a blinded, parallel study in which they received a placebo, 10 mmol/day calcium carbonate (CaCO 3 ), or 20 mmol/day CaCO 3 . There were no significant differences in blood pressure changes among the groups. In the hypertensive group and in patients with the highest blood pressure there were individual falls in systolic pressure, particularly in the group receiving 10 mmol daily A number of studies investigating the effect of calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Doses ranged from 10-50 mmol/day (0.4-2 g/day) of calcium, 10-40 mmol/day (0.2-1 g/day) of magnesium, and 48-120 mmol/day (0.5-1.2 g/day) of potassium. Control groups received placebo [106][107][108][109][110][111]113,114,[116][117][118][119][120][121][122][123][124][125][126][127][128]130,131,[133][134][135][136] or no treatment [93,112,115,129].…”
Section: Combined Interventionsmentioning
confidence: 99%
“…Doses ranged from 10-50 mmol/day (0.4-2 g/day) of calcium, 10-40 mmol/day (0.2-1 g/day) of magnesium, and 48-120 mmol/day (0.5-1.2 g/day) of potassium. Control groups received placebo [106][107][108][109][110][111]113,114,[116][117][118][119][120][121][122][123][124][125][126][127][128]130,131,[133][134][135][136] or no treatment [93,112,115,129].…”
Section: Combined Interventionsmentioning
confidence: 99%
“…habitual) calcium intake. One trial tested different doses of calcium with a single control group 34 and three trials tested multiple formulations of calcium with a single control group. 32,33,46 For these trials, BP changes in the intervention groups were averaged and extracted from BP change in the control group.…”
Section: Extraction Of Study Characteristicsmentioning
confidence: 99%
“…28 If different publications on identical studies were found, we used all available information for data abstraction and cited the most recent publication. 34,52 One trial in which all subjects participated in the parallel phase and part of the subjects in a crossover phase was treated as if it had a parallel design. 50 Imputations were made for mean age, based on the midpoint of the age range, in one trial, 24 gender (i.e.…”
Section: Extraction Of Study Characteristicsmentioning
confidence: 99%
“…15 However, a randomized controlled trial of calcium supplementation in older New Zealand women showed only a small and transient hypotensive effect in most women, the effect being more marked in those with a calcium intake of o600 mg day À1,16 and no effect in normotensive or hypertensive people in another study. 17 A recent Cochrane Database analysis concluded that the causal relationship between calcium supplementation on blood pressure is weak. 18 Earlier studies in Chinese populations showed a positive association between sodium intake, 19 but an inverse association with calcium intake was only observed in older vegetarian women, among whom the prevalence of osteoporosis is high.…”
Section: Introductionmentioning
confidence: 99%